Penerapan Telemedicine terhadap Penyembuhan Luka Kaki Diabetik Grade IV Paska Amputasi - Nila Indrayati; Debie Dahlia; Riri Maria (Journal of Telenursing (JOTING), 2021)
This study aims to describe the healing process of diabetic foot wounds monitored through telemedicine during the Coronavirus disease-19 pandemic. The method used in this study was a case report of a 64-year-old patient with a history of grade IV diabetic foot injuries after amputation of the thumb on the right foot. The time needed to do telemedicine as a medium for monitoring wound conditions and education is about 30 minutes. The results showed that wound healing was significantly successful, within one month, as many as ten dressing changes with a duration of once every three days. In conclusion, telemedicine contributes positively to efforts to heal diabetic foot wounds. Keywords: Case Report, COVID-19, Diabetic Foot Sores, Telemedicine